Application of artificial neural network to predict slug liquid holdup. (May 2022) - Abdul-Majeed, Ghassan H.; Kadhim, F.S.; Almahdawi, Falih H.M.; Al-Dunainawi, Yousif; Arabi, A.; Al-Azzawi, Waleed Khalid
Abstract: This work demonstrates the artificial neural network (ANN) ability for predicting slug liquid holdup ( HLS ), using 2525 measured points from 20 experimental studies. Six variables, including superficial gas velocity ( VSG ), superficial liquid velocity, liquid viscosity, pipe diameter, pipe inclination (ø), and surface tension, are selected as inputs to the ANN. The optimum ANN structure obtained is 6-11-1, with tangent sigmoid as an activation function. The developed ANN performs best and outperforms 12 existing HLS models compared with present data and independent data. A sensitivity analysis shows that Ø has the lowest impact, whereas VSG is the most significant variable on ANN-HLS . To demonstrate the impact of ANN-HLS on pressure drop in pipes, a mathematical model is derived and combined with the slug mechanistic models of Zhang et al. (2003) and Abdul-Majeed and Al-Mashat (2000) . Based on Tulsa University Fluid Flow Project field measured data (1712 well cases), the new mathematical model's incorporation results in better predictions than using the individual HLS correlations of these two models. The statistical results indicate that the slug model of Zhang et al. (2003) with ANN-HLS and modified Barnea map gives the best performance compared to the existing pressure models. Graphical abstract: Image, graphical abstract